The Concept of Asy-Syifā’ in the Qur’an: An Analysis of Surah An-Nahl Verse 69 from the Perspective of Tafsir Al-Misbah - Mardhiah Mardhiah; Husnaini Husnaini; Bobby Fahreza; Muhammad Syahrial Razali Ibrahim (Electronic Journal of Education, Social Economics and Technology, 2025)
The Qur'an, as the word of God, serves various purposes in life, including healing diseases (syifa). As-syifā' in the Qur'an describes the function of the Qur'an as a healer for diseases, both physical and spiritual. Asy-Syifā' in the perspective of M. Quraish Shihab's interpretation of al-Mishbah emphasizes that the healing referred to in the Qur'an is not only spiritual and moral in nature, but also includes the physical dimension. Quraish Shihab also highlights that healing does not come solely from God but must also be accompanied by human effort. The Qur'an, Surah An-Nahl, verse 69, Quraish Shihab, through the interpretation of Al-Misbah, bees and honey as symbols of moral and social examples, where honey is a healing gift, and bees are an image of creatures that are obedient, productive, and provide benefits to all. This study uses a literature review approach (library research), namely examining various academic sources such as books, scientific journals, research reports, and official documents relevant to Asy-Syifā’ in the Qur’an: Analysis of Surah An-Nahl Verse 69 from the Perspective of Al-Misbah's Interpretation. The purpose of this study is to examine honey as a treatment for physical ailments in Surah An-Nahl Verse 69.